(untitled) (Orchid Insights: A Multidisciplinary Journal of Orchid College, 2026)
This study aims to examine the relationship between perceived social support and self-esteem among Nepalese young adults. Perceived social support refers to an individual’s perception of the availability and adequacy of emotional, informational or instrumental assistance from family, friends, and significant others. Self-esteem refers to an individual’s overall evaluation of self-worth or personal value, reflecting positive or negative attitudes towards oneself. For this study the sample consisted of N = 171 college students aged between 18–24 years. Reliable and valid instruments were used to measure study variables. Self-esteem was assessed using the Rosenberg Self-Esteem Scale (RSES) and perceived social support was measured using the Multi-Dimensional Scale of Perceived Social Support (MSPSS). The results of the analysis revealed no significant association between perceived social support and self-esteem (r = −0.147, p = 0.055). Significant associations were observed among the subscales of perceived social support, including support from family, friends, and significant others. Findings of this study show that perceived social support does not directly influence self-esteem of Nepalese young adults and highlight the necessity of further research with more psychosocial and cultural variables.